<span>4 2/5 - 1 7/10
= </span><span>4 4/10 - 1 7/10
= 3</span> 14/10 - 1 7/10
= 2 7/10
answer
<span>2 7/10</span>
Answer:
<h2>90</h2>
Step-by-step explanation:
Substitute a = -3 and b = -8 to the expression 10a²b⁰:
10(-3)²(-8)⁰ = 10(9)(1) = 90
a⁰ = 1 for any real number
Answer:
1/3^2
Im trying to earn my brainliest..so if you don't mind :)
Answer:
Step-by-step explanation:
Gym A has a $150 joining fee and costs $35 per month.
Assuming that Casey wants to attend for x months, the cost of using gym A will be
150 + 35 times x months. It becomes
150 + 35x
Gym B has no joining fee and costs $60 per month.
Again, assuming that Casey wants to attend for x months, the cost of using gym B will be
60 × x months = 60x
A) To determine the number of months that it will both gym memberships to be the same, we will equate them.
150 + 35x = 60x
60x - 35x = 150
25x = 150
x = 150/25 = 6
It will take 6 months for both gym memberships to be the same.
B) If Casey plans to only go to the gym for 5 months,
Plan A will cost 150 + 35×5 = $325
Plan B will cost 60 × 5 = $300
Plan B will be cheaper